Synthesis and Application of a Near-Infrared Light-Emitting Fluorescent Probe for Specific Imaging of Cancer Cells with High Sensitivity and Selectivity - Li S; Lin Z; Chen H; Luo Q; Han S; Huang K; Chen R; Zhan Y; Chen B; Yao H (Dove Medical Press, 2024)
Shaoguang Li,1 Zhan Lin,1 Haobo Chen,1 Qiu Luo,1 Shengnan Han,1 Kunlong Huang,1 Ruichan Chen,1 Yuying Zhan,1 Bing Chen,2 Hong Yao1- 3 1Department of Pharmaceutical Analysis, School of Pharmacy, Fujian Medical University, Fuzhou, FuJian, People's Republic of China; 2Higher Educational Key Laboratory for Nano Biomedical Technology of Fujian Province, Fujian Medical University, Fuzhou, Fujian, People's Republic of China; 3Fujian Key Laboratory of Drug Target Discovery and Structural and Functional Research, Fujian Medical University, Fuzhou, Fujian, People's Republic of ChinaCorrespondence: Shaoguang Li; Hong Yao, Department of Pharmaceutical Analysis, School of Pharmacy, Fujian Medical University, 1 Xue Yuan Road, University Town, Fuzhou, Fujian, 350122, People's Republic of China, Email lsg941@126.com; yauhung@126.comBackground: The preclinical diagnosis of tumors is of great significance to cancer treatment. Near-infrared fluorescence imaging technology is promising for the in-situ detection of tumors with high sensitivity.Methods: Here, a fluorescent probe was synthesized on the basis of Au nanoclusters with near-infrared light emission and applied to fluorescent cancer cell labeling. Near-infrared methionine-N-Hydroxy succinimide Au nanoclusters (Met-NHs-AuNCs) were prepared successfully by one-pot synthesis using Au nanoclusters, methionine, and N-Hydroxy succinimide as frameworks, reductants, and stabilizers, respectively. The specific fluorescence imaging of tumor cells or tissues by fluorescent probe was studied on the basis of SYBYL Surflex-DOCK simulation model of LAT1 active site of overexpressed receptor on cancer cell surface. The results showed that Met-NHs-AuNCs interacted with the surface of LAT1, and C_Score scored the conformation of the probe and LAT1 as five.Results: Characterization and in vitro experiments were conducted to explore the Met-NHs-AuNCs targeted uptake of cancer cells. The prepared near-infrared fluorescent probe (Met-NHs-AuNCs) can specifically recognize the overexpression of L-type amino acid transporter 1 (LAT1) in cancer cells so that it can show red fluorescence in cancer cells. Meanwhile, normal cells (H9c2) have no fluorescence.Conclusion: The fluorescent probe demonstrates the power of targeting and imaging cancer cells.Keywords: Au nanoclusters, fluorescence imaging, cancer cell imaging, molecular docking